2011
DOI: 10.1038/bmt.2011.90
|View full text |Cite
|
Sign up to set email alerts
|

M-CSF attenuates severity of chronic GVHD after unrelated BMT

Abstract: To study the effects of M-CSF administration on longterm outcomes of unrelated BMT, we retrospectively analyzed data from patients transplanted through the Japan Marrow Donor Program. We obtained data from 54 patients who received M-CSF just after BMT and 500 patients who did not receive M-CSF or G-CSF acted as controls. There were no significant differences between the two cohorts with respect to OS, acute GVHD or relapse. Although the incidence of chronic GVHD was comparable between the two groups, extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Because M-CSF treatment reduces graft-versus-host disease in allogeneic HCT ( Hashimoto et al, 2011 ; Kimura et al, 2012 ), it will be important to determine whether it also has a protective effect against infection in this setting, as suggested by earlier retrospective clinical observations ( Nemunaitis et al, 1993 ). In this context, the influence of M-CSF treatment on graft-versus-leukemia effects and on residual malignant cells will also require further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Because M-CSF treatment reduces graft-versus-host disease in allogeneic HCT ( Hashimoto et al, 2011 ; Kimura et al, 2012 ), it will be important to determine whether it also has a protective effect against infection in this setting, as suggested by earlier retrospective clinical observations ( Nemunaitis et al, 1993 ). In this context, the influence of M-CSF treatment on graft-versus-leukemia effects and on residual malignant cells will also require further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The observed monocytosis highlights the importance of further studying the etiology of cGVHD, which might be related to chronic inflammation, as observed in autoimmune processes (40) or functional asplenia (41). Macrophage colony-stimulating factor (M-CSF) is a well-known inducer of monocytosis, and its administration to patients undergoing HSCT was shown to attenuate cGVHD (42), implicating that also, after HSCT, elevated M-CSF levels might drive monocyte expansion and alleviate cGVHD. Higher absolute monocyte counts were related with cGVHD, future cGVHD onset, higher NRM rate, as well as poor outcomes of allogeneic HSCT (43), and vice versa , monocyte recovery during the first year after HSCT may be associated with better outcome (44).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that IL‐34‐macrophages are more efficient to expand Tregs than CSF‐1‐macrophages and those Tregs are highly suppressive as they delay GVHD development in immune humanized NSG mice 25 . In human clinical trials, the protective role of CSF‐1 administration needs to be further investigated because some results showed improved recovery associated with less development of chronic GVHD 174,175 . However, another study indicated neither beneficial or deleterious role of CSF‐1 administration 176 .…”
Section: Overlapping and Non‐overlapping Functions Of Il‐34 And Csf‐1 In Diseasesmentioning
confidence: 96%